The Kacirebonan Gamelan Music Accompaniment in Ergonomic Exercise and Its Impact on Blood Pressure Hypertensive Elderly - Omay Rohmana; Ati Siti Rochayati; Dian Yuniar Syanti Rahayu; Susi Susanti (Direktorat Politeknik Kesehatan Makassar, 2025)
Ergonomic exercise has been recommended for older adults with hypertension. However, initially, it was carried out without music. Kacirebonan gamelan music is a traditional music that has characteristics of music therapy. The research objective is to determine the effects of ergonomic exercises accompanied by kacirebonan gamelan music and those not accompanied by kacirebonan gamelan music on systolic and diastolic blood pressure in hypertensive elderly in Cirebon. The research design is a quasi-experimental pretest-posttest intervention with two treatment groups: the first received ergonomic exercise accompanied by kacirebonan gamelan music, and the second received ergonomic exercise only. The intervention was carried out daily for 12 days, with two sessions per day, each lasting about 30 minutes, every 9 hours in the morning. The sample size was formulated by (t-1) (r-1) > 15, so the sample for each group consisted of 16 hypertensive elderly and 32 people for the whole sample, selected by simple random sampling and meeting the inclusion and exclusion criteria. Data analysis was performed using a t-test based on the Shapiro-Wilk normality test, with a p-value> 0.05. The result: there was no significant difference between before and after the intervention in systolic pressure (p=0.787>0,05) and diastolic pressure (p=0.229>0,05) in hypertensive elderly in the treatment group. There was no significant difference between the treatment and control groups in systolic pressure (p = 0.468 > 0.05) or diastolic pressure (p = 0.761 > 0.05) after treatment in hypertensive elderly. Ergonomic exercise without the accompaniment of kacirebonan gamelan music produces a greater effect on systolic (0.036 < 0.05) and diastolic (0.045 < 0.05) blood pressure in hypertensive elderly. The research conclusion is that the accompaniment of kacirebonan gamelan music during ergonomic exercises did not have a significant effect on systolic or diastolic blood pressure in elderly hypertensives. Ergonomic exercise without the accompaniment of kacirebonan gamelan music had a greater impact on reducing systolic and diastolic pressure in hypertensive elderly in Cirebon. Future research should formally operationalise and measure participants' cultural perceptions and expectations of an intervention before implementation.